Sensor-Based Nerve Compression Measurement: A Scoping Review of Current Concepts and a Preclinical Evaluation of Commercial Microsensors - Daeschler, Simeon C.; Wienbruch, Rebecca; Bursacovschi, Catalina; Zimmermann, Kim Sophie; Nemariam, Selam Bekure; Harhaus, Leila; Kneser, Ulrich; Dehé, Alfons; Bittner, Achim (Frontiers in Bioengineering and Biotechnology, 2022)
Background: Chronic nerve compression is the most common indication for nerve surgery. However, the clinical diagnosis still relies on surrogate parameters since devices for direct nerve compression pressure measurement (DNCPM) are clinically unavailable yet. Objectives: Reviewing previous approaches to DNCPM and evaluate presently available microsensor-systems for their feasibility and reliability in preclinical nerve compression models. Methods: A scoping literature review was conducted in accordance with the PRISMA-ScR-guidelines. A subsequent market research aimed at identifying commercially available sensor systems potentially suitable for DNCPM. Sensors were evaluated for feasibility and safety of perineural sensor positioning, tissue compatibility and measurement reliability in a synthetic nerve compression model and an ex-vivo chicken leg model Results: A scoping literature review identified 197 potentially eligible studies of which 65 were included in the analysis. Previous approaches to DNCPM predominantly used pressure sensing catheters designed for fluid- or intra-compartmental pressure measurement. A market research identified two piezoresistive sensor systems (IntraSense, SMi, USA; Mikro-Cath, Millar, USA) as potentially suitable for intraoperative DNCPM. In both preclinical models, the detected compression pressure differed significantly between sensors and systems showed substantial measurement variability with a median percent coefficient of variation between 15.5 % to 32%. Sensor position was accountable for up to 99.1% of the variance. Conclusion: Measurement variability caused by unreliable sensor positioning is a key limitation of presently available sensors when applied for nerve compression measurements. Redesigned systems with small, flat-shaped and longitudinally oriented sensors and dedicated introducers would facilitate sensor positioning and therefore may allow for reliable measurements.